2013
DOI: 10.1111/1460-6984.12022
|View full text |Cite
|
Sign up to set email alerts
|

Use of Spatial Communication in Aphasia

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(15 reference statements)
1
5
0
Order By: Relevance
“…As hypothesised, and consistent with previous studies (Cruice et al, 2014 ; Johnson et al, 2013 ; Ulatowska et al, 1981 ; Webster et al, 2007 ), PWA in the current study produced syntactically and semantically less complex language in their discourses. However, contrary to hypotheses and the majority of previous studies (Cicone et al, 1979 ; Cocks et al, 2013 ; Feyereisen, 1983 ; Hadar et al, 1998 ; Herrmann et al, 1988 ; Lanyon & Rose, 2009 ; Orgassa, 2005 ; Sekine et al, 2013 ), both groups used similar quantities and types of gestures.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As hypothesised, and consistent with previous studies (Cruice et al, 2014 ; Johnson et al, 2013 ; Ulatowska et al, 1981 ; Webster et al, 2007 ), PWA in the current study produced syntactically and semantically less complex language in their discourses. However, contrary to hypotheses and the majority of previous studies (Cicone et al, 1979 ; Cocks et al, 2013 ; Feyereisen, 1983 ; Hadar et al, 1998 ; Herrmann et al, 1988 ; Lanyon & Rose, 2009 ; Orgassa, 2005 ; Sekine et al, 2013 ), both groups used similar quantities and types of gestures.…”
Section: Discussionsupporting
confidence: 92%
“…First, for example, PWA use fewer Correct Information Units (defined as any single word, intelligible, informative, and relevant in context) in discourse than NHP (Nicholas & Brookshire, 1993 ). Second, PWA also use fewer types and tokens of spatial language in spatial tasks than NHP (Johnson, Cocks, & Dipper, 2013 ). Finally, speakers with aphasia and verb production deficits also use verbs differently to speakers without verb production deficits, using a high level of semantically “light” verbs containing little semantic information, such as come, go, make, take, get, give, do, have, be , and put (Berndt et al, 1997 ).…”
Section: Aphasia and Discoursementioning
confidence: 99%
“…2018). Johnson et al (2013) reported marked differences in the abilities of their participants to use gesture to compensate for their difficulties accessing verbal spatial language, arguing that this indicated the importance of clinicians investigating the language and gesture profile of individuals with aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…However, other researchers have argued that, if confounding factors such as limb apraxia and comprehension impairments are controlled for, people with aphasia's gesture production can remain functional, even when language is severely impaired (Akhavan et al 2018). Johnson et al (2013) reported marked differences in the abilities of their participants to use gesture to compensate for their difficulties accessing verbal spatial language, arguing that this indicated the importance of clinicians investigating the language and gesture profile of individuals with aphasia.…”
mentioning
confidence: 99%
See 1 more Smart Citation